Heart rate variability of dogs living in restricted spaces - Busato, Pamela Regina Pimenta; Gnoatto, Fernando Luis Cemenci; Champion, Tatiana (Semina: Ciências Agrárias, 2025)
When animal welfare conditions are not met, stress can occur. Among other effects, this may lead to cardiovascular alterations related to sympathovagal imbalance. This study aimed to integrate heart rate variability (HRV) analysis with a welfare assessment of eight dogs allocated into groups with and without space restriction to determine the influence of space restriction stress using current methods. The study was conducted in the dogs’ home environments, with 24-hour ambulatory electrocardiogram recordings. Welfare was assessed in both hospital and home settings using the five-domain model, behavioral analysis, and stress evaluation. Data were analyzed statistically, with significance set at p < 0.05. The results showed higher welfare scores particularly in the environmental (p < 0.001) and behavioral (p = 0.0002) domains for dogs without space restrictions. There was no difference in HRV indices over 24 hours. Continuous space restriction was found to be detrimental to various animal needs, and dogs in this group showed clear welfare shortcomings. The HRV findings may indicate that restricted dogs did not experience greater activation of the sympathetic autonomic nervous system due to their environment though this does not imply that their welfare was unaffected. In conclusion, HRV analysis did not differ between dogs with or without space restriction; however, the five-domain model and stress assessment revealed welfare deficiencies in restricted dogs.